Treatment of lumbar brucella spondylitis with negative pressure wound therapy via extreme lateral approach: A case report - Cui, Haocheng; Chang, Zhengqi; Yu, Xiuchun (Frontiers in Surgery, 2022)
Brucella spondylitis (BS) is a specific spinal infection. Surgical treatment is required for Brucella spondylitis that has caused neurological symptoms in the lower extremities and developed an intraspinal abscess. The main purpose of surgery is to remove the lesion and restore the stability of the spine. However, both the anterior approach and the posterior approach cannot completely remove the lesions, resulting in a low cure rate and a certain recurrence rate. Although anterior or posterior debridement is more thorough, it is unbearable for some patients with poor general condition. In this study, for the first time, a negative pressure wound therapy (NPWT) device was introduced into the intervertebral space through the extreme lateral approach to treat a patient with Brucella spondylitis. We summarize the treatment process, and discuss the feasibility and effectiveness of this surgical approach through 1-year follow-up.